Transcranial direct current stimulation alleviates the pain severity in people suffering from knee osteoarthritis: a systematic review and meta-analysis - Tian Dai; Meng Liu; Dapeng Bao; Brad Manor; Junhong Zhou (PAIN Reports)
Abstract. Considerable research has shown the benefits of transcranial direct current stimulation (tDCS) for the alleviation of pain associated with knee osteoarthritis (KOA). Still, a large variance in study protocols and observations across publications exists. We here thus completed a systematic review and meta-analysis to comprehensively and quantitatively characterize the effects of tDCS on KOA-related pain. A search strategy based on the Population, Intervention, Comparison, Outcome, and Study design (PICOS) principle was used to obtain the publications in 7 databases. Studies exploring the effects of tDCS on KOA-related pain were screened, and eligible studies were included. Ten studies of 518 participants using Visual Analogue Scale or Numeric Rating Scale to assess pain were included in the systematic review, and 9 of them were included in meta-analysis. The quality of these studies was good. Compared to control, tDCS induced significant short-term improvements in KOA-related pain with medium heterogeneity (standardized mean difference [SMD] = −0.91, 95% confidence interval [−1.24, −0.58], P < 0.001, I2 = 61%). Subgroup analyses showed that both home-based (SMD = −1.32, 95% CI [−1.65, −0.99], P < 0.001, I2 = 0%) and laboratory-based intervention (SMD = −0.66, 95% CI [−0.99, −0.33], P < 0.001, I2 = 40%) with at least 5 sessions per week (SMD = −1.02, 95% CI [−1.41, −0.64], P < 0.001, I2 = 65%) and/or with a total number of at least 10 sessions (SMD = −1.12, 95% CI [−1.51, −0.74], P < 0.001, I2 = 59%) can induce maximum benefits for the alleviation of KOA-related pain. The results here showed that tDCS is of great promise to alleviate KOA-related pain. Still, future studies with more rigorous design are needed to confirm the observations from this work, which can ultimately help the determination of appropriate intervention protocol that can maximize such benefits.